2005
DOI: 10.1152/ajpgi.00268.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofibrate stimulates the gastrin-producing cell by acting luminally on antral PPAR-α

Abstract: dum. Ciprofibrate stimulates the gastrin-producing cell by acting luminally on antral PPAR-␣. Am J Physiol Gastrointest Liver Physiol 289: G1052-G1062, 2005. First published August 11, 2005; doi:10.1152/ajpgi.00268.2005.-The lipid-lowering drug ciprofibrate stimulates gastrin-producing cells in the rat stomach without lowering gastric acidity. Although suggested to be a luminal action on antral peroxisome proliferator-activated receptor-␣ (PPAR-␣), the mechanism is still not fully elucidated. Gastric bypass w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Shortly thereafter it was realized that the competitive H2RA ranitidine also caused ECL cell tumours, when given the dose needed to achieve prolonged acid inhibition [18]. Further studies have demonstrated that ECL cell tumours in the corpus remnant may also be induced by partial corpectomy causing hypergastrinemia [19,20] or by administration of ciprofibrate, a drug that induces hypergastrinemia without altering gastric acidity [21,22,23]. Transgenic INS-GAS mice have hypergastrinemia accompanied by gastric hyperacidity and develop tumours in the gastric corpus with an adenocarcinoma phenotype [24].…”
Section: Resultsmentioning
confidence: 99%
“…Shortly thereafter it was realized that the competitive H2RA ranitidine also caused ECL cell tumours, when given the dose needed to achieve prolonged acid inhibition [18]. Further studies have demonstrated that ECL cell tumours in the corpus remnant may also be induced by partial corpectomy causing hypergastrinemia [19,20] or by administration of ciprofibrate, a drug that induces hypergastrinemia without altering gastric acidity [21,22,23]. Transgenic INS-GAS mice have hypergastrinemia accompanied by gastric hyperacidity and develop tumours in the gastric corpus with an adenocarcinoma phenotype [24].…”
Section: Resultsmentioning
confidence: 99%
“…Ciprofibrate, a peroxisome proliferator-activated receptor α (PPAR-α) agonist, given by oral gavage, increases gastrin secretion, associated with a doubling of G cell density in the stomach antrum of Sprague-Dawley rats (Martinsen et al 2005). This did not occur in gastricbypassed rats and PPAR-α -/mice (Martinsen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofibrate, a peroxisome proliferator-activated receptor α (PPAR-α) agonist, given by oral gavage, increases gastrin secretion, associated with a doubling of G cell density in the stomach antrum of Sprague-Dawley rats (Martinsen et al 2005). This did not occur in gastricbypassed rats and PPAR-α -/mice (Martinsen et al 2005). PPAR-α agonists have been reported also to increase progastrin production in human colorectal carcinoma cells (Lachal et al 2004), but this mechanism has not been studied in normal human stomach G cells.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term administration of the competitive H2-blocker ranitidine also has the ability to induce ECL cell carcinoids when given in large enough doses [22]. Finally, the administration of ciprofibrate induces ECL cell carcinoids [23] in rats without gastric hypoacidity [24], but causes hypergastrinemia through a direct effect on the antral G-cell [25]. The induction of ECL cell carcinoids by ciprofibrate clearly demonstrates that it is hypergastrinemia and not hypoacidity that drives ECL cell carcinogenesis.…”
Section: Animal Modelsmentioning
confidence: 99%